Knowledge Transfer-Based School Management as a Model for Improving Learning Quality: A Case Study in Elementary Schools - Sri Wahyuningsih; Ghufron Abdullah; Qristin Violinda (Journal of Educational Sciences, 2026)
The increasing demand for improving educational quality requires schools to adopt innovative and collaborative management approaches. This study aims to analyze the implementation of school management based on knowledge transfer at SD Negeri 03 Doro, Pekalongan Regency. The research employs a qualitative approach with a case study design to explore in depth the processes, mechanisms, and impacts of knowledge transfer in improving school management quality. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the implementation of knowledge transfer-based management has been carried out systematically through planning, organizing, implementing, and evaluating functions. Knowledge transfer occurs through collaborative activities such as mentoring, coaching, co-teaching, and sharing best practices among teachers. This process contributes significantly to improving teachers’ competencies, instructional quality, and participatory decision-making. Furthermore, it strengthens school governance and enhances community trust. The novelty of this study lies in integrating knowledge transfer as a structured managerial strategy in primary school management, rather than merely informal knowledge sharing. However, the study is limited to a single research site and constrained by variations in teacher competencies and resource availability. Future research is recommended to expand the scope and apply mixed methods to obtain more comprehensive findings.